Growth and development of reproductive buds of Prunus persica cv. Goosen at two localities during autumn, winter and spring - Pretorius, Willem J.(Willem Jacobus) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. (Agric.)) -- University of Stellenbosch, 1970.